Inflammatory Processes Associated with Canine Intervertebral Disc Herniation - Monchaux, Marie; Forterre, Simone; Spreng, David; Karol, Agnieszka; Forterre, Franck; Wuertz-Kozak, Karin (Frontiers in Immunology, 2017)
Intervertebral disc herniation (IVDH) is an important pathology in humans, but also in dogs. While the molecular disease mechanisms are well investigated in humans, little is known about the inflammatory mediators in naturally occurring canine IVDH. The objective of this study was to investigate whether the involved pro-inflammatory cytokines in human IVDH are also key cytokines in canine IVDH and thus to elucidate the suitability of the dog as a model for human trials. 59 samples from 25 dogs with surgically confirmed thoracolumbar IVDH were collected and classified in three subgroups: herniated (H), affected non-herniated disc (NH) and adjacent non-affected disc (NA). Discs from 11 healthy dogs acted as controls (C). Samples were analyzed for IL-1, IL-6, IL-8 and TNF-α expression (qPCR/ELISA) as well as cell infiltration and activation of the MAPK pathways (immunohistochemistry). Gene and protein expression of all key cytokines could be detected in IVDH affected dogs. Canine IVDH was significantly associated with a higher gene expression of IL-6 (H>C, NH>C) and TNF-α (H>C, NH>C, NA>C) and a significant down-regulation of IL-1β (H<C). Dogs with spontaneous pain had significantly higher IL-6 mRNA compared to those with pain arising only upon palpation. An inter-donor comparison (H and HN relative to NA) revealed a significant increase of IL-6 gene expression (H>NA, NH>NA). IL-8 (H>C, NA>C) and TNF-α (NH>C) protein levels were significantly increased in diseased dogs while inversely, IL-6 protein levels were significantly higher in patients with better clinical outcome. Aside from resident IVD cells, mostly monocytes and macrophages were found in extruded material, with concomitant activation of ERK and p38 in the majority of samples. Dogs with spontaneous IVDH might provide a useful model for human disc diseases. Although the expression of key cytokines found in human IVDH was also demonstrated in canine tissue, the inflammatory mechanisms accompanying canine IVDH diverges partially from humans, which will require further investigations in future. In dogs, IL-6 seems to play an important pathological role and may represent a new potential therapeutic target for canine patients.